(untitled) (Physical Education, Health and Social Sciences, 2026)
The high price and low accessibility of commercial 3-axis CNC milling machines is a challenge that many small businesses and educational establishments face. Consequently, affordable and accessible CNC machines that offer reliable machining are needed in training and light production. This work explores the design, implementation, and performance assessment of a compact low-cost 3-axis CNC machine for small enterprise and academic applications. The machine utilizes an aluminum frame, lead screws with anti-backlash nuts, linear guides and NEMA 17 stepper motors to drive the X, Y and Z axes. Control system implemented on Arduino Uno operated via GRBL firmware performs the task of carrying out G-code operations, controlled through open-source CNC software. The CNC prototype was developed and calibrated for the evaluation of kinematic accuracy and operational performance. Observations from experiments show axis positioning precision in the range of ±0.05–0.10 mm and maintaining repeatability up to ±0.05 mm. Machining trials on wood, aluminum and acrylic exhibit dependable multi-material cutting capabilities resulting in a smooth and consistent surface. The CNC machine, with an approximate cost of 450 USD, provides a cost-effective alternative to commercial CNC machines for prototyping, training, and light manufacturing applications.